The impact of overall obesity on serotonin level in the acute phase of coronavirus infection and post-coronavirus sequelae: aspects of neuropsychological and cognitive impairments - O. V. Zinych; N. M. Kushnarova; A. A. Shuprovych; O. M. Trofymenko (Zaporožskij Medicinskij Žurnal)
Aim: to study the relationship between neurotransmitter support and the degree of cognitive and psycho-emotional impairments in patients in the post-coronavirus period depending on the presence of overall obesity.